IoT- Based Smart Security System Using Infrared Sensor as Motion Detector - Muhamad Riyad Ariwibowo; Juju Juhaeriyah; Edo Agung Nugroho; Rendi Mutaqim (ITEJ (Information Technology Engineering Journals), 2023)
Today’s security system requires the support of new technology to make it easier to monitor remotely and maintain valuables stored at home in real time. Internet of things technology has now been widely developed with various types of electronic components applied. So, from these problems providing innovation with the development of a remote security system applied to the FC-51 infrared sensor and ESP8266 as it’s control. The infrared sensor receives input signals in the form of objects detected and received by ESP8266 to be sent information to the server to be notified of messages from the Blynk platform to mobile devices. The results of this study prove, that the smart security system with IoT – based infrared sensor is able to detect the optimal distance obtained < 30cm and the shape of different objects determines the level of accuracy of the sensor.